Efek Profitabilitas, Solvabilitas, dan Opini Audit Terhadap Audit Report Lag: (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Wirawan Widjanarko; Hadita; Della Alvionita Putri; Y.A Didik Cahyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of profitability, solvency, and audit opinion on audit report lag. This study uses descriptive statistical analysis using a quantitative approach with purposive sampling method. In this study, secondary data is used in the form of an annual report published successively during 2018-2020 on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The population in this study are all Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange for the 2018-2020 period. A total of 96 companies are data samples. The analytical method used is Multiple Linear Regression. This study uses data analysis methods that include descriptive statistical analysis and classical assumption test to test the feasibility of using the regression model. The classical assumption test used in this study includes the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Multiple regression analysis in this study was used to examine the effect of the independent variables, namely profitability, solvency, and audit opinion on the dependent variable, namely audit report lag. In this study, SPSS version 23 software was used to obtain the results of the tests carried out. So the results of this study indicate that profitability, solvency and audit opinion have no effect on audit report lag.